THE DEVELOPMENT OF GEOMETRY SONG-BASED AUDIO LEARNING MEDIA USING REALISTIC MATHEMATICS EDUCATION MODEL ON PLANE FIGURE MATERIALS - Wibowo Septiani; Siti Ruqoyyah; Sylvia Rabbani (Sekolah Pascasarjana UPI, 2022)
This research is motivated by students who often mistakenly determine the formula for perimeter and area of plane figures. Therefore, we need a learning media to help students remember and understand the formula for the circumference and area of a flat shape. The purpose of this research is to determine the process, feasibility of developing audio learning media based on Geometry Song using the Realistic Mathematics Education model. This study uses the Research and Development (RD) method. The subjects in this study were 10 fourth grade students during the limited test and 26 students during the broad test in one of the elementary schools in West Bandung. The research instrument used consisted of field notes and validation sheets. Field note sheets are used to determine the process and results of the development of the developed learning media and validation sheets to determine the feasibility of the developed media. The results of the study showed that the Geometry Song-based audio learning media using the Realistic Mathematics Education model obtained a percentage of 98.7% from the assessment of material experts, while the assessment of media experts and practitioners obtained a percentage of 100%, from the results of these percentages it can be said that the developed media is